2020
DOI: 10.13106/jafeb.2020.vol7.no9.537
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Ease of Use, Perceived Usefulness, Perceived Security and Intention to Use E-Filing: The Role of Technology Readiness

Abstract: This study aimed to analyze evidence of the effect of perceived ease-of-use, perceived usefulness, and perceived security on the citizen's intention to use e-Filing with information technology readiness as an intervening variable. This study used primary data collected from Civil Servants Taxpayers, Indonesian National Armed Forces, and State Police of the Republic of Indonesia in Semarang City. One hundred fifty questionnaires were distributed, and 126 were processed and analyzed. The multiple linear regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
104
2
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(136 citation statements)
references
References 30 publications
18
104
2
12
Order By: Relevance
“…H2a, which was not supported in the current study, did not confirm the findings of the TAM (Davis, 1989) and TAM2 (Venkatesh & Davis, 2000) models. However, this is in accord with the findings of many studies in the literature such as Tahar et al (2020) and Oum and Han (2011) which did not find any significant effect of the perceived usefulness on the intention to use new technology. This result indicates that the usefulness of an information technology does not always lead to the intention to use or attitude towards the use of the system.…”
Section: Discussionsupporting
confidence: 90%
“…H2a, which was not supported in the current study, did not confirm the findings of the TAM (Davis, 1989) and TAM2 (Venkatesh & Davis, 2000) models. However, this is in accord with the findings of many studies in the literature such as Tahar et al (2020) and Oum and Han (2011) which did not find any significant effect of the perceived usefulness on the intention to use new technology. This result indicates that the usefulness of an information technology does not always lead to the intention to use or attitude towards the use of the system.…”
Section: Discussionsupporting
confidence: 90%
“…Most people may be sceptical about using a technological device or system because they have no experience with the usefulness of the system. A recent study by Tahar et al (2020) also found an insignificant result for the direct relationship between PE (perceived usefulness in the study) and intention to use e-filing in Indonesia.…”
Section: Performance Expectancycontrasting
confidence: 52%
“…In particular, previous literature indicated that TAM consistently accounts for 40% of variance in usage intention and behaviors (Venkatesh & Davis, 2000). TAM has been widely examined and validated and is an extensively accepted model in different sorts of technologies related to user and organization acceptance and adoption such as the World Wide Web (Lederer, Maupin, Sena, & Zhuang, 2000;Van der Heijden, 2004;Tahar, Riyadh, Sofyani, & Purnomo, 2020), Intranet (Horton, Buck, Waterson, & Clegg, 2001), E-commerce (Olson & Boyer, 2003;Pavlou, 2003;Han, Thao Nguyen, & Nguyen, 2016), Internet Banking (Aldás-Manzano, Lassala-Navarré, Ruiz-Mafé, & Sanz-Blas, 2009, Mobile banking (Le, Trinh, & Nguyen, 2020;Phuong, Luan, Dong, & Khanh, 2020) that lead to their widespread acceptance.…”
Section: Theoretical Backgroundmentioning
confidence: 99%